The neuro-invasive potential of severe acute respiratory syndrome coronavirus 2 - Qayyum, Fabiha; Malik , Muna; Malik , Muhammad Irfan (International Journal of Endorsing Health Science Research, 2021)
Severe Acute Respiratory Syndrome-CoronaVirus-2 (SARS-CoV-2) induced coronavirus disease (COVID-19) presents with several neurological manifestations just like other Beta Corona Virus (βCoV) family members. SARS-CoV-2 affects the central nervous system (CNS) in many ways eliciting various neurological disorders generally from headaches, ataxia, mental confusion to severe respiratory distress, and eventually death. The different portals of access of SARS-CoV-2 into the CNS, i.e., hematogenous and neuronal retrograde motion, increase the incidence of neurological manifestations and poor disease prognosis. A new idea regarding neuro-invasion of SARS-CoV-2, i.e., its potential of latency and possible later reactivation and complications, has been presented. This aims to direct the attention towards research to determine the impact range of latency and reactivation of SARS-CoV-2. Keeping in view, these aspects finding SARS-Cov-2 in cerebrospinal fluid (CSF) by reverse transcriptase-polymerase chain reaction (RT-PCR) and complete CSF examination should be employed.